Digital multimedia concepts, methodologies, tools, and applications (Information Science Reference, 2018)
"This book is an innovative source of scholarly content on the latest trends, perspectives, techniques, and implementations of multimedia technologies. Including a comprehensive range of topics such as interactive media, mobile technology, and data management"--